Child safety from the perspective of essential needs - Mello, Débora Falleiros De; Henrique, Nayara Cristina Pereira; Pancieri, Letícia; Veríssimo, Maria De La Ó Ramallo; Tonete, Vera Lúcia Pamplona [UNESP]; Malone, Mary (Escola de Enfermagem de Ribeirão Preto / Universidade de São Paulo, 2014)
OBJECTIVE:to characterize the maternal care for children under one year of age with a view to child health promotion at home.METHOD:exploratory study with qualitative data analysis, thematic mode, based on the conceptual framework of the essential needs of children, based on interviews recorded with 16 mothers.RESULTS:the analysis of the maternal narratives showed elements that facilitate the promotion of child safety: presence and involvement of the parents, constant surveillance for physical and emotional protection, experiences to stimulate child development, support networks for childcare at home; and inhibiting elements of child safety: limited perception of characteristics of child development and of children's singularities, overprotection and difficulties to set limits.CONCLUSION:the study enhances the understanding of home care in child health promotion, directing professional actions to guarantee ongoing nurturing relationships, protection, respect for individual differences, experiences appropriate to child development, limit setting and construction of stable and supportive social networks. In addition, the relevance of considering the maternal perspective in child health care is considered, as a strategy to apprehend aspects related to the attendance of the growth and development needs, particularly for child health promotion at home.

OBJETIVO: caracterizar os cuidados maternos às crianças menores de um ano para a promoção da segurança infantil no domicílio. MÉTODO: estudo exploratório, com análise qualitativa dos dados, modalidade temática, fundamentado no quadro conceitual das necessidades essenciais da criança, a partir de entrevistas gravadas com 16 mães. RESULTADOS: a análise das narrativas maternas mostrou elementos facilitadores da promoção da segurança infantil: presença e envolvimento dos pais, vigilância constante para proteção física e emocional, experiências estimuladoras do desenvolvimento, redes amparadoras para o cuidado da criança no domicílio; e elementos inibidores da segurança infantil: pouca percepção das características do desenvolvimento infantil e das singularidades da criança, superproteção e dificuldades para estabelecimento de limites. CONCLUSÃO: o estudo amplia a compreensão sobre o cuidado domiciliar na promoção da saúde infantil, orientando ações profissionais para garantir relacionamentos sustentadores contínuos, proteção, respeito às diferenças individuais, experiências adequadas ao desenvolvimento, estabelecimento de limites e construção de redes sociais estáveis e amparadoras. Também reafirma a relevância de se considerar as perspectivas maternas no cuidado da saúde da criança, como estratégia para apreender aspectos relacionados ao suprimento das necessidades do crescimento e desenvolvimento, particularmente à promoção da segurança infantil no domicílio.

OBJETIVO: caracterizar los cuidados maternos a menores de un año para la promoción de la seguridad infantil en el domicilio. MÉTODO: estudio exploratorio, con análisis cualitativo de los datos, modalidad temática, fundamentado en el cuadro conceptual de las necesidades esenciales del niño, a partir de entrevistas grabadas con 16 madres. RESULTADOS: el análisis de las narraciones maternas mostró elementos facilitadores de la promoción de la seguridad infantil: presencia y participación de los padres; vigilancia constante para protección física y emocional; experiencias estimuladoras del desarrollo; redes de amparo para el cuidado del niño en el domicilio; y, elementos inhibidores de la seguridad infantil (poca percepción de las características del desarrollo infantil y de las singularidades del niño, sobreprotección y dificultades para establecimiento de límites). CONCLUSIÓN: el estudio amplia la comprensión sobre el cuidado domiciliar en la promoción de la salud infantil, orientando acciones profesionales para garantizar relaciones sustentadores continuas, protección, respeto a las diferencias individuales, experiencias adecuadas al desarrollo, establecimiento de límites y construcción de redes sociales estables y de amparo. También reafirma la relevancia de considerar las perspectivas maternas en el cuidado de la salud del niño, como la estrategia para aprender aspectos relacionados al suministro de las necesidades del crecimiento y desarrollo, particularmente para la promoción de la seguridad infantil en el domicilio.
A segurança da criança na perspectiva das necessidades essenciais
La seguridad del niño en la perspectiva de las necesidades esenciales
Keywords: Criança; Promoção da Saúde; Enfermagem; Child; Health Promotion; Nursing